Relation between endothelial nitric oxide synthase genetic polymorphisms and pulmonary arterial hypertension in newborns with congenital heart disease - Qing-Fan Lin; Jing-Hong Rao; Shi-Mu Luo; Qing-Mu Wang; Li-Feng Deng; Xuan Chen; Chang-Di Chen; You-Fang Chen (Clinical and Experimental Hypertension, 2022)
Objective To investigate whether endothelial nitric oxide synthase (eNOS) rs1799983, rs2070744, and rs61722009 gene polymorphisms are associated with pulmonary arterial hypertension (PAH) in South Fujian newborns with congenital heart disease (CHD). Methods Genotyping for the eNOS rs1799983, rs2070744, and rs61722009 polymorphisms was performed using Sanger sequencing in 50 newborns with PAH secondary to CHD [CHD PAH (+)], 52 newborns with CHD without PAH [CHD PAH (-)], and 60 healthy controls. Results The genotype and allele frequency distributions of eNOS rs1799983, rs2070744, and rs61722009 were similar between CHD and healthy controls (P > .05). The frequencies of the eNOS rs1799983 G/T allele were 85% and 15% in the CHD PAH (+) group and 96.15% and 3.85% in the CHD PAH (-) group, the frequency of the T allele was higher in the CHD PAH (+) group than in the CHD PAH (-) group(P< .05), and patients with the GT/TT genotypes of eNOS rs1799983 may present higher PAH (OR = 4.412, 95%CI:1.411–13.797, P= .011). Newborns with the GT/TT genotypes had decreased plasma NO production compared to newborns with the GG genotype (P< .01), and NO levels in the CHD PAH (+) group were significantly lower than those in the CHD PAH (-) group (P < .05). Conclusion The T allele could be a risk factor for PAH in newborns with CHD in South Fujian through decreased levels of nitric oxide production by the endothelium.